Implementasi QR Code untuk Efisiensi Waktu Pemesanan Menu Makanan dan Minuman di Restoran maupun Kafe - Suharianto; Lukman Bahar Agung Pambudi; Angga Rahagiyanto; Gandu Eko Julianto Suyoso (Puslitbang Sinergis Asa Professional, 2020)
The quick response (QR) code provides a fast, easy, convenient, accurate and automatic method of transporting data. By freeing applications and popularizing wireless communications and cellular technology, two-dimensional barcode technology has been used for production, logistics, and sales. To order the benefits of technology to the service sector, for this study, we used various QR code applications in the food or beverage menu service management system in restaurants / cafes. The specific purpose is to allow restaurant waiters to quickly and appropriately provide service to restaurant / cafe customers. Experimental results show that the method developed in this study can significantly improve the service menu, prepare waiters and chefs to provide the right service, shorten the time for ordering the menu, and facilitate the resolution of the problem. Research in actual circumstances will be a full support tool for restaurant / cafe menu services. The results of the test prove agreeing from the point of view of efficiency and cost savings, the new system is fast and efficient, improving very competitive with the release of an improved management system.